Association between iron‐deficiency anemia and depression: A web‐based Japanese investigation. Issue 7 (9th May 2018) - Hidese, Shinsuke; Saito, Kenji; Asano, Shinya; Kunugi, Hiroshi
Abstract : Aim: This web‐based survey aimed to examine the relation between iron‐deficiency anemia and depression in 11 876 Japanese participants. Methods: Participants consisted of 1000 individuals with self‐reported history of depression (mean age, 41.4 ± 12.3 years; 499 women) and 10 876 population‐based controls (mean age, 45.1 ± 13.6 years; 5185 women). The 6‐item Kessler Scale (K6) score was used as a psychological distress scale. The design of the study was cross‐sectional. Results: The rate of self‐reported lifetime history of iron‐deficiency anemia was higher in the depression group in both men (depression, 7.2%; control, 4.0%; P  < 0.001; odds ratio [OR], 1.86; 95% confidence interval [CI], 1.30–2.68) and women (depression, 33.4%; control, 25.8%; P  < 0.001; OR, 1.45; 95%CI, 1.19–1.76). The K6 score in participants with self‐reported history of iron‐deficiency anemia was higher in both the depression ( P  = 0.004) and control ( P  < 0.001) groups. In addition, in all participants, the rate of individuals who showed a K6 cut‐off score of 13 or more was higher in those with a self‐reported history of iron‐deficiency anemia ( P  < 0.001; OR, 1.47; 95%CI, 1.31–1.65). Logistic regression analyses revealed that self‐reported history of depression and the K6 score were positively associated with self‐reported history of iron‐deficiency anemia (all P  < 0.01). Conclusion: Self‐reported history of iron‐deficiency anemia was associated with self‐reported history of depression. Furthermore, self‐reported history of iron‐deficiency anemia was associated with higher psychological distress.